Pengembangan FMEWS Berbasis IoT dan MQTT untuk Peringatan Banjir - I Komang Darma Wiguna; Ketut Agus Seputra; Kadek Yota Ernanda Aryanto (TIN: Terapan Informatika Nusantara, 2026)
Floods are disasters that frequently cause physical, social, and economic losses, including in Buleleng Regency, Bali. The main problem in flood mitigation lies in delayed early warning delivery and the absence of a centralized platform that integrates field monitoring data with operational disaster management data. This study aims to design and develop the Flood Monitoring and Early Warning System (FMEWS) based on the Internet of Things (IoT) and the Message Queuing Telemetry Transport (MQTT) protocol to support real-time flood monitoring and early warning. The system was developed using the Waterfall model of the System Development Life Cycle (SDLC) and consists of IoT devices, an IoT Gateway, and a web-based information system integrating water level monitoring, early warning notifications, shelter management, public facility management, community reports, and spatial visualization. The novelty of this study lies in integrating real-time IoT-based flood monitoring with operational disaster management data into a single centralized platform. The results show that a transmission rate of 2–5 Hz provides the best balance between latency and communication reliability, with a Packet Delivery Ratio (PDR) of at least 96.67%. Usability testing involving 22 respondents produced an average System Usability Scale (SUS) score of 70.0, which falls into the Acceptable category. These findings indicate that FMEWS is feasible as a supporting platform for flood monitoring and early warning in Buleleng Regency.